1984
DOI: 10.1002/clc.4960070201
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of patients with postinfarction angina caused by coronary artery spasm

Abstract: tion in the remaining 3. All patients performed a treadmill exercise stress test before discharge and most demonstrated excellent tolerance. All patients experienced no form of chest pain for an average of 25 months follow-up under medication. We conclude that among patients with postinfarction angina, those cases caused by coronary artery spasm have a relatively good prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Coronary artery spasm as a cause of postinfarction angina is debated,22.23 and may represent a group with a relatively good prognosis. 24 Nifedipine and diltiazem are proposed as effective therapy that would obviate bypass surgery in this subset of pat i e n t~.~~. '~ Verapamil was found to be ineffective in controlling postinfarction ischemia or reinfarction."…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery spasm as a cause of postinfarction angina is debated,22.23 and may represent a group with a relatively good prognosis. 24 Nifedipine and diltiazem are proposed as effective therapy that would obviate bypass surgery in this subset of pat i e n t~.~~. '~ Verapamil was found to be ineffective in controlling postinfarction ischemia or reinfarction."…”
Section: Discussionmentioning
confidence: 99%
“…Previously we were convinced that postinfarction angina caused by coronary artery spasm was easily suppressed by oral calcium antagonists and/or nitrates (Koiwaya et al, 1982(Koiwaya et al, , 1984Nakamura and Koiwaya, 1983). However, the recent experience of patient l in the present communication has revealed that in some patients it is difficult to abolish postinfarction angina caused by coronary artery spasm.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent experience of patient l in the present communication has revealed that in some patients it is difficult to abolish postinfarction angina caused by coronary artery spasm. To search for a way to eliminate postinfarction angina refractory to such routine medication, tiding over the "unstable state" is important, since such patients seem to enjoy a relatively good clinical course after complete suppression (Koiwaya et al, 1984). Many noninvasive and invasive methods should be tried for the control, and the most appropriate treatment must be determined as soon as possible.…”
Section: Discussionmentioning
confidence: 99%